The synergistic interaction between ACE and TMPRSS2 polymorphisms increases the risk of severe COVID-19 - Odonchimeg Bayaraa; Chimedlkhamsuren Ganbold; Bayarlakh Byambadorj; Zolzaya Battulga; Ichinnorov Dashtseren; Sarantuya Jav (PLoS ONE, 2026)
Within a few years after the pandemic outbreak, several of evidence have found to suggest that the genetic factors influence the severity and mortality rate of COVID-19. In particular, the identification of genetic markers that increase the risk of severe or critical COVID-19 is important for public health management during the pandemic. By August 2021, 88.9% of Mongolian population had been vaccinated. Therefore, we conducted this study to compare the polymorphisms of candidate genes by selecting people who developed mild or severe COVID-19 within this vaccinated population. A total of 90 patients with severe COVID-19, 95 patients with mild COVID-19, and 90 asymptomatic patients were participated in present cross-sectional study. rs4646994, rs4240157, rs41423247, rs56149945, rs10052957, rs12329760, rs4303795, rs75603675 and rs17854725 polymorphisms of the ACE , ACE2 , NR3C1 and TMPRSS2 genes were genotyped. Genotyping performed by real-time PCR, RFLP and allele-specific PCR methods. Odds ratio, 95% confidence interval, p value were calculated using logistic regression analysis. SNP-SNP interaction were explored using multi-dimensional reduction analysis. P values for multivariate model was corrected by Bonferroni correction. Totally 10 polymorphisms of above-mentioned genes were genotyped among the groups. Only A/C genotype frequencies of rs75603675 were significantly different between groups. Compared with mild COVID-19 group, the participants who carrying A/C genotype of rs75603675 had 3.58-fold (95% CI, 1.38–9.29, p = 0.009) higher risk for severe COVID-19. In addition, the synergistic interaction (RERI = 2.573; AP = 0.934; S = 8.352) was observed between D/D or I/D genotype of rs4646994 and A/C genotype of rs75603675, which combination (OR=4.88, 95% CI, 1.38–18.01, p = 0.014, Power = 91.1%) was associated with increased risk of severe COVID-19 after Bonferroni correction. Our result suggesting that the combination of rs4646994 of the ACE gene and rs75603675 of the TMPRSS2 gene is associated with increased risk of severe COVID-19.